Violation of Legal Certainty in the Sale and Purchase Deed made by the Land Deed Officer (PPAT) - Devarinta Hayyu Anandari; Adi Sulistyono; Suraji Suraji (Westscience Press, 2023)
The regional revenue Office (Bapenda) and the Land Office apply the inclusion of Bapenda's appraisal price in the Sale and Purchase Deed made by the Land Deed Making Officer (PPAT). If this happens, then there will be no legal certainty for the parties. This happens mainly because the PPAT Sale and Purchase Deed is an authentic deed and has an important role in proving civil cases, especially if there is a dispute in court. Authentic Deeds have the highest position as documentary evidence in civil cases, below which are private deeds and unilateral deeds or unilateral confessions. The evidentiary value of an authentic deed based on Article 1870 of the Civil Code is perfect (volledig bewijskracht) and binding (bindede bewijskracht). This has consequences, whatever is stated in the authentic deed must be considered true and valid. Apart from that, the contents and statements contained therein are true.